2010
DOI: 10.1007/s12011-010-8719-9
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Disorders—Assessments of Trace Elements, Clinical, and Laboratory Parameters

Abstract: The trace elements studied in this work (Se, Cu, Zn) are the essential constituents or cofactors required to activate numerous enzymes and proteins, playing crucial role in various physiological processes. The disturbed levels of abovementioned elements may adversely affect the endocrine system, resulting in various thyroid disorders among other upsets. The aim of this study was to investigate possible associations between them and parameters of redox balance, thyroid function indices as well as clinical recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 35 publications
3
21
1
4
Order By: Relevance
“…Copper metabolism in the blood and tissues has already been shown to change in thyroid diseases [23]. Additionally, thyroid cancer patients were reported to have elevated blood copper concentrations [12,24] and iron deficiency was reported to alter copper levels in the rat brain tissue [10]. Elevated serum copper levels we found in our study are consistent with the results of the studies cited above.…”
Section: Discussionsupporting
confidence: 91%
“…Copper metabolism in the blood and tissues has already been shown to change in thyroid diseases [23]. Additionally, thyroid cancer patients were reported to have elevated blood copper concentrations [12,24] and iron deficiency was reported to alter copper levels in the rat brain tissue [10]. Elevated serum copper levels we found in our study are consistent with the results of the studies cited above.…”
Section: Discussionsupporting
confidence: 91%
“…One study showed significant elevation [107], the other showed significant decrease [105] and third, ranked as high quality [106], found no significant differences. No publication bias was observed.…”
Section: Resultsmentioning
confidence: 83%
“…In many studies on animal models, as well as in epidemiological and interventional surveys, beneficial effects were confirmed of normal or even increased serum selenium concentrations on the initiation, progression, and even metastases of various cancer types but not of thyroid cancer [50,102]. The relationship between selenium supplementation and the incidence of thyroid cancer has been verified in many clinical studies (Table I); however, it has not been unequivocally confirmed, especially in the Polish population [103][104][105][106][107][108][109][110][111]. The access to mainly retrospective data, the relatively small groups of patients, and the short observation periods, as well as only single assays of selenium concentration levels, were all significant limitations in the performed studies.…”
Section: Prace Poglądowementioning
confidence: 99%
“…W wielu badaniach na modelach zwierzęcych oraz epidemiologicznych i interwencyjnych stwierdzono korzystny wpływ prawidłowych, a nawet podwyższonych stężeń selenu w surowicy na inicjację, progresję, a nawet przerzuty różnych rodzajów nowotworów, ale nie raka tarczycy [50,102]. Związek pomiędzy zaopatrzeniem w selen i występowaniem raka tarczycy został zweryfikowany w wielu badaniach klinicznych (Tabela I) i w metaanalizie, jednakże nie został jednoznacznie potwierdzony, zwłaszcza w polskiej populacji [103][104][105][106][107][108][109][110][111]. Dostęp głównie do danych retrospektywnych, relatywnie małe grupy pacjentów i krótki czas obserwacji oraz pojedyncze oznaczenia zaopatrzenia w selen stanowią istotne ograniczenia przeprowadzonych badań.…”
Section: Prace Poglądoweunclassified